Incentives for Smoking Cessation During Pregnancy: An Ethical Framework. Issue 9 (18th December 2019) - Breunis, Leonieke J; Been, Jasper V; de Jong-Potjer, Lieke; Steegers, Eric Ap; de Beaufort, Inez D; de Kroon, Marlou La; Ismaili M'hamdi, Hafez
Abstract: Introduction: Smoking during pregnancy increases the risk of morbidity and mortality of the mother and child. The inability of the unborn child to protect itself, raises the social and academic responsibility to protect the child from the harmful effects of smoking. Interventions including rewards (incentives) for lifestyle changes are an upcoming trend and can encourage women to quit smoking. However, these incentives can, as we will argue, also have negative consequences, for example the restriction of personal autonomy and encouragement of smoking to become eligible for participation. To prevent these negative consequences, we developed an ethical framework that enables to assess and address unwanted consequences of incentive-based interventions whereby moral permissibility can be evaluated. Aims and Methods: The possible adverse consequences of incentives were identified through an extensive literature search. Subsequently, we developed ethical criteria to identify these consequences based on the biomedical ethical principles of Beauchamp and Childress. Results: Our framework consists of 12 criteria. These criteria concern (1) effectiveness, (2) support of a healthy lifestyle, (3) motivational for the target population, (4) stimulating unhealthy behavior, (5) negative attitudes, (6) personal autonomy, (7) intrinsic motivation, (8) privacy, (9) fairness, (10) allocation of incentives, (11) cost-effectiveness, and (12) health inequity. Based on these criteria, the moral permissibility of potential interventions can be evaluated. Conclusions: Incentives for smoking cessation are a response to the responsibility to protect the unborn child. But these interventions might have possible adverse effects. This ethical framework aims to identify and address ethical pitfalls in order to avoid these adverse effects. Implications: Although various interventions to promote smoking cessation during pregnancy exist, many women still smoke during pregnancy. Interventions using incentives for smoking cessation during pregnancy are a promising and upcoming trend but can have unwanted consequences. This ethical framework helps to identify and address ethical pitfalls in order to avoid these adverse effects. It can be a practical tool in the development and evaluation of these interventions and in evaluating the moral permissibility of interventions using incentives for smoking cessation during pregnancy.